2011
DOI: 10.1002/app.34421
|View full text |Cite
|
Sign up to set email alerts
|

New polymer syntheses part: 54 novel conducting polymers and copolymers based on 4‐Teriary butyl‐cyclohexanone moiety in the main chain

Abstract: A new interesting class of conducting polymer and copolymers based on 4-teriary butyl-cyclohexanone in the main chain has been synthesized by solution polycodensation of terephthalaldehyde with 4-teriary butylcyclohexanone and/or cycloalkanone derivatives. The model compound I was synthesized from the 4-teriary butyl-cyclohexanone with benzaldehyde, and its structure was confirmed by elemental and spectral analyses. The resulting polymer and copolymers were characterized by elemental and spectral analyses incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Various mathematical equations are used in literature for calculating the intrinsic viscosity [η] of a polymeric solution, by graphic extrapolation (eqn. [1][2][3][4] and from a single point viscometry measurement of dilute solution (eqn. [5][6].…”
Section: Preparation Of 44'-methylenebis(cinnamaldehyde) (Mbc) and Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Various mathematical equations are used in literature for calculating the intrinsic viscosity [η] of a polymeric solution, by graphic extrapolation (eqn. [1][2][3][4] and from a single point viscometry measurement of dilute solution (eqn. [5][6].…”
Section: Preparation Of 44'-methylenebis(cinnamaldehyde) (Mbc) and Tmentioning
confidence: 99%
“…Characterization of this polymer has been done extensively by techniques like infrared spectroscopy (FTIR), ultraviolet/visible spectroscopy (U/V spectroscopy) and nuclear magnetic resonance (NMR). The thermal analysis as well viscosity measurement was observed from these derived Schiff base polymers 2,3 . The solubility of bis(cinnamaldehyde) and their Schiff base polymeric solutions were taken in highly polar solvents (DMF/THF) at 30 ºC 4 , to investigate viscometric study by dilute solution viscometry (DSV) method.…”
Section: Introductionmentioning
confidence: 96%
“…However, LC polyesters have not been receiving the deserved focus and attention. After performing extensive work on these polymers, Kamal I Aly and coworkers [15][16][17], observed that the main advantages of benzylidene polyesters are lower melting temperatures, broader mesophase stability range and higher solubility. A pioneering work by Aminabhavi et al [18,19] and Percec et al [20,21] in the field of liquid crystalline polyethers and polyesters covers many aspects related to this field.…”
Section: Introductionmentioning
confidence: 99%
“…As a continuation of the work reported in the literature concerning the variable studies on the synthesis and properties of different new polymers based on diarylidenecycloalkanones possessing an interesting properties, attractive morphology, higher thermal stability, liquid crystalline behavior, corrosion protection, conducting properties, antimicrobial activity and many other properties, which have been presented in the literature [11][12][13][14][15][16][17][18]. Furthermore, different arylidene conjugated polymers, copolymers and terpolymers were synthesized and studied [19][20][21]. In this research work we present a route for the synthesis and characterization of some new arylidene polymers, and copolymers containing methyl-cyclohexanone moiety in the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%